Conservative Management of Cervical Radiculopathy: A Systematic Review. Issue 3 (2nd March 2023) - Plener, Joshua; Csiernik, Ben; To, Daphne; da Silva-Oolup, Sophia; Hofkirchner, Corey; Cox, Jocelyn; Cancelliere, Carol; Chow, Ngai; Hogg-Johnson, Sheilah; Ammendolia, Carlo
Abstract : Objective: The purpose of this systematic review was to assess the effectiveness and safety of conservative interventions compared with other interventions, placebo/sham interventions, or no intervention on disability, pain, function, quality of life, and psychological impact in adults with cervical radiculopathy (CR). Methods: We searched MEDLINE, CENTRAL, CINAHL, Embase, and PsycINFO from inception to June 15, 2022 to identify studies that were randomized controlled trials, had at least one conservative treatment arm, and diagnosed participants with CR through confirmatory clinical examination and/or diagnostic tests. Studies were appraised using the Cochrane Risk of Bias 2 tool and the quality of the evidence was rated using the Grades of Recommendations, Assessment, Development, and Evaluation approach. Results: Of the 2561 records identified, 59 trials met our inclusion criteria (n = 4108 participants). Due to clinical and statistical heterogeneity, the findings were synthesized narratively. There is very-low certainty evidence supporting the use of acupuncture, prednisolone, cervical manipulation, and low-level laser therapy for pain and disability in the immediate to short-term, and thoracic manipulation and low-level laser therapy for improvements in cervical range of motion in the immediate term. There is low to very-low certainty evidence for multimodal interventions, providing inconclusive evidence for pain, disability, and range of motion. There is inconclusive evidence for pain reduction after conservative management compared with surgery, rated as very-low certainty. Discussion: There is a lack of high-quality evidence, limiting our ability to make any meaningful conclusions. As the number of people with CR is expected to increase, there is an urgent need for future research to help address these gaps.